Trans Students in Italian Schools: Challenges and Best Practices (European journal of volunteering and community-based projects, 2024)
Scientific literature focusing on the experience of trans students highlights how schools are a hostile place for trans people, who are subjected to repeated forms of physical and verbal aggression, bullying, and transphobic harassment by the peer group, teaching, and non-teaching staff. To counter these issues and recognise the identity and needs of trans people, schools have introduced the alias career, a tool already present in Italian universities since 2012. The device outlines good practices to protect the well-being of transgender students and improve their school experience. The regulations of the institutes that have introduced the alias career show that in Italy, the trans experience is still strongly pathologised to the extent that medical-psychological documentation is often required for its activation. Moreover, many good practices are absent or implemented incorrectly, such as toilet access, changing rooms, or training for the school staff and the student body. With this article, the authors, by considering the Italian education system's peculiarities, propose good practices that can help improve the alias career by supplementing it with new proposals that allow students to be recognised and protected during their years of schooling. A further aim is to guide the school staff in responding to the needs of trans pupils and bringing change within the school context by restructuring cisnormative value systems.
Keywords: Career alias; transgender students; inclusive education; best practices; school